Comparative Analysis of Radiofrequency Ablation and Microwave Ablation for Critically Located Hepatocellular Carcinomas Smaller than 5 cm - Ravindran Ramalingam; Amar Mukund; Karan Manoj Anandpara; Yashwant Patidar; Shiv Kumar Sarin (Journal of Clinical Interventional Radiology ISVIR)
Purpose To compare the safety and efficacy of radiofrequency ablation (RFA) versus microwave ablation (MWA) for hepatocellular carcinomas (HCC) smaller than 5 cm in critical locations. Methods Single-center retrospective study of all patients who underwent RFA/MWA for HCC from July 2015 to Dec 2019. Critical location includes exophytic tumors, tumors ≤ 5 mm from the diaphragm, heart, gallbladder, kidney, gastrointestinal tract, and ≤ 10 mm from large vessels with caliber of ≥ 3 mm. Treatment effectiveness, local tumor progression, and complication rates were evaluated. Results Out of 119 patients with 147 HCC nodules in critical location, 65 (M:F = 49:16; mean age–61.7) were included in RFA group and 54 (M:F =43:11; mean age–60.5) in MWA group. Mean follow-up period was 16.5 and 14.8 months, respectively. At first follow-up imaging, 66/78 tumors in RFA group and 57/69 tumors in MWA group showed complete ablation with primary treatment effectiveness rates of 84.6% and 82.6%, respectively (p = 0.741). Local tumor progression (LTP) rate was 21.8% (17/78) and 20.3% (14/69), respectively (p = 0.826). Median time to LTP was 12 and 13.5 months, respectively. Fourteen tumors in RFA group and 12 in MWA group underwent reablation with a secondary treatment effectiveness rates of 78.6% (14/17) and 83.3% (12/14), respectively (p = 0.757). Mean LTP-free survival was 37.2 and 28.1 months, respectively. The total complication rate was 36.9% and 31.5%, respectively (p = 0.535) with no major complications in both the groups. Conclusion Our data suggest that both MWA and RFA are equally safe and effective for treating HCCs < 5 cm in critical locations.